Mechanisms of host manipulation by Neisseria gonorrhoeae - Walker, Emma; van Niekerk, Stacy; Hanning, Kyrin; Kelton, William; Hicks, Joanna (Frontiers in Microbiology, 2023)
Neisseria gonorrhoeae (also known as gonococcus) has been causing gonorrhoea in humans since ancient Egyptian times. Today, global gonorrhoea infections are rising at an alarming rate, in concert with an increasing number of antimicrobial-resistant strains. The gonococcus has concurrently evolved several intricate mechanisms that promote pathogenesis by evading both host immunity and defeating common therapeutic interventions. Central to these adaptations is the ability of the gonococcus to manipulate various host microenvironments upon infection. For example, the gonococcus can survive within neutrophils through direct regulation of both the oxidative burst response and maturation of the phagosome; a concerning trait given the important role neutrophils have in defending against invading pathogens. Hence, a detailed understanding of how N. gonorrhoeae exploits the human host to establish and maintain infection is crucial for combating this pathogen. This review summarizes the mechanisms behind host manipulation, with a central focus on the exploitation of host epithelial cell signaling to promote colonization and invasion of the epithelial lining, the modulation of the host immune response to evade both innate and adaptive defenses, and the manipulation of host cell death pathways to both assist colonization and combat antimicrobial activities of innate immune cells. Collectively, these pathways act in concert to enable N. gonorrhoeae to colonize and invade a wide array of host tissues, both establishing and disseminating gonococcal infection.